Investigation of Spot Size Variations in Multiroom Proton Therapy Systems and Their Clinical Significance: An In silico Study - Umesh Bharat Gayake; Bhushankumar J. Patil; Kantaram Darekar; Sanjay D. Dhole; Lalit Chaudhary; Siddhartha Laskar (Journal of Medical Physics)
Background and Purpose: In multiroom proton therapy facilities, maintaining beam consistency is critical, particularly when treatment interruptions occur due to machine downtime. Among beam parameters, spot size frequently exceeds tolerance limits, potentially compromising treatment accuracy. This study aims to assess the clinical implications of spot size variations and establish benchmarks for beam matching, with a specific focus on the spot size parameter in proton therapy using tool for particle simulation (TOPAS), Monte Carlo (MC) simulation. Materials and Methods: The study analyzed the effects of spot size deviations (±0.3 mm and ± 0.6 mm) on proton therapy treatment plans using TOPAS MC simulations. The five variable spot sizes models were created in the RayStation treatment planning system by simulating the known spot size shift error in the TOPAS for 33 proton energies ranging from 70.18 to 226.2 MeV. These models were evaluated using both homogeneous phantom fields and heterogeneous clinical fields targeting the pelvis, brain, and prostate. Key dosimetric metrics target, coverage (TC), conformity index, and homogeneity index, were assessed. In addition, two-dimensional gamma analysis was performed at tolerances of 1%/1 mm, 2%/2 mm, and 3%/2 mm to quantify the clinical impact of spot size variations on treatment delivery accuracy. Results: The evaluation indicated that Model −0.6 mm achieved the highest target coverage (TC), while Model 0.6 mm resulted in the lowest. Comparative analysis within the homogeneous phantom revealed marked variations in TC and conformity indices among the tested models. Clinical investigation revealed that TC in the pelvic area was constant, but that TC in the brain and prostate was more sensitive to changes in spot size. Gamma analysis showed superior passing rates for the model ± 0.3 mm, particularly at 2%/2 mm and 3%/2 mm criteria, confirming its suitability for optimal treatment accuracy. Conclusion: Spot size variations significantly influence the accuracy of proton therapy, with deviations of ± 0.3 mm yielding the most favorable results. Adhering to this tolerance ensures consistent beam matching and precise treatment delivery across various clinical sites, supporting the reliability of multiroom proton therapy systems.